A Role of Therapy that Targets Immune Checkpoint Proteins for the Treatment of Melanoma Brain Metastasis, Liver, Breast, Pancreatic Cancer and Pancreatic Adenocarcinoma - Mohammed, Smaa Elsayed; Youssef, Basma Aml; Ghonai, Doaa Alaa; Ahmed, Eman Fares; Mohammed, Esraa Gharieb; Abdo, Mai Ashraf; Mohammed, Mai Essam; Hassan, Rana Gharieb; Mohammed, Reem Mohammed; Abd Al-Azeem, Rofida Ahmed; Swelem, Sarah Adel; Salman, Sarah Ouda; et al. (AL-Kindy College Medical Journal, 2022)
Checkpoint inhibitors are a type of immune therapy used to treat different types of cancers. These drugs block different checkpoint proteins, for example, CTLA-4, PD-1, and PD-L1 inhibitors.They block proteins that stop the immune system from attacking the cancer cells.  Checkpoints are also described as a type of monoclonal antibody that antagonizes binding between B7 to CTLA-4 and PD-L1 to PD-1. Immune checkpoint inhibitors are used to treat BARCA mutated triple-negative breast cancer (TNBCS) in patients who do not respond to chemotherapy, and also in the treatment of highly mutated and solid tumors such as brain tumors, liver, and pancreatic cancers.Immune checkpoint inhibitors exhibit an effect on solid tumors by suppressing CTLA-4, PD-1, and PDL-1. Anti-PD-1 is less toxic than anti-CTLA-4.For melanoma Brain metastasis immune checkpoint therapy is more effective and Combination therapy has great efficacy and less toxicity which improves overall survival rather than individual therapyliver cancer as hepatocellular carcinoma and cholangiocarcinoma used treatment with Genetics based therapy while using alternative immune checkpoint ligands, co-inhibitory (eg. LAG-3) or decreased t-cell infiltration causing therapy failure.Clinical studies for pancreatic cancer have not been completed yet and treating PDA needs more research as immune checkpoint inhibitors is a new treatment against  PDA. A new potent class of nivolumab, pembrolizumab, and ipilimumab have been FDA approved.For mutated tumors, Combination therapy between checkpoint inhibitors and chemotherapy has great efficacy and improves the city of life and overall survival, rather than individual therapy when using radiation or chemotherapy alone.